Openness of Public Information at Regional Representative Institutions In Carrying out the Function of the Regional House of Representatives - Hikmat, Mahi M (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2019)
Law No. 14 of 2008 on public information transparency (KIP), must implement the information transparency. One of the Government Public Councils whose accessibility of information transparency to public is Regional House of Representatives (DPRD). DPRD has two different functional structures, consisting of leadership with DPRD complementary organs and secretariat. DPRD should have strategy in the implementation of KIP and it was in the study entitled The Policy Implementation of Regional House of Representatives in Public Information Transparency. Inductive data analysis was conducted through of the data simplification processes into a more readable and interpretable form. This study employed the statutory approach and descriptive qualitative method to reveal the strategies applied by DPRD in implementing KIP. This normative legal research took data from regulation of law relating to KIP. The result of the study shows that the law of KIP provides an obligation to DPRD as an